Measuring Britain's Merchant Shipbuilding Output in the Twentieth Century. - Buxton, Ian; Fenton, Roy; Murphy, Hugh (Mariner's Mirror, 2015)
This article reports on work done to arrive at a reliable estimate of British shipbuilding output in the twentieth century. Three datasets are considered: the annual figures of the Shipbuilding Conference, those of Lloyd's Register and those of the British Shipbuilding Database (BSD). Differences between the figures are explored and reconciliation attempted by examining the sources used by compilers of the datasets in order to arrive at what is believed to be the most accurate estimate yet attempted of British shipbuilding output in the twentieth century. The article is notable in that for the first time a table of completions has been compiled for the entire century.